Does Corporate Governance Affect the Capital Structure Decisions of Omani Listed Companies? - Sariman, Ahmed Sultan Salmen (2011)
This paper explores the relationship between corporate governance and capital structure of listed firms in an emerging equity market, Oman. The study looked at 87 non-financial listed companies on the Muscat Securities Market and was examined by using multivariate regression analysis. Measurements of corporate governance employed are bankers on board, board ownership, and interlocking directorates. The impact of controlled variables like firm size, profitability and age on firms’ financing mechanism were also investigated. The results revealed that interlocking directorates was significantly and positively correlated with debt to equity ratio. However, corporations’ financing behavior was not found to be significantly influenced by board ownership. The results revealed that a banker on board was significantly and negatively correlated with ratio of debt to equity, suggesting the firms in Oman were usually large family-owned business groups with concentrated ownership. The board of directors (banker-directors) may serve the purpose of family controlling shareholders. Furthermore, banker-directors were influenced by the Arabic traditional values and norms (e.g., personal relations, preference for individuals from influential tribes, etc.) which might affect their orientations and behavior. However, control variables, firm profitability was found to have a significant and negatively associated with the capital structure. Firm size and firm age were not found to be significantly associated with the capital structure.